Knowledge and Attitude’s of Semarang Dental Therapist about Fluoride as Caries Prevention Modalities - Diyah Fatmasari; Eksa Sinta; Sadimin Sadimin (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2021)
Caries is caused by germs and processed carbohydrates, exacerbated by the frequency of sucrose and can be modified by fluoride and saliva. The use of fluoride as a prevention material for dental cavities is very important. Dental Therapist must have knowledge about fluoride in order to determine attitudes in the use of fluoride. The purpose of this study was to determine differences in knowledge and attitudes of dental and oral therapists about fluoride as a preventative material for caries prevention.Research design was observational analytic with cross sectional approach. The research data was obtained using a questionnaire as instruments. Respondents was 44 dental therapist who works at Semarang Community Health Service. Chi-square test was used as an analysis tool with a value of p 0.05.The results showed differences between Dental Therapists' knowledge of fluoride by age group (p = 0,000), but there were no differences in knowledge by sex group (p = 0.674) and education level (p = 0.831). There was a difference between the attitude of the Dental Therapist based on age group (p = 0.049), but there was no difference based on gender group (p = 0.220) and education level (p = 0.534).Based on these results, it can be concluded that there are differences in the knowledge and attitudes of Dental and Oral Therapists towards fluoride with the age group, the older the age then tend to have positive behavior and can also understand and digest the proper use of fluoride and how to minimize the incidence of dental fluorosis